The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10237-018-1076-x
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic device with spatiotemporal wall shear stress and ATP signals to investigate the intracellular calcium dynamics in vascular endothelial cells

Abstract: Intracellular calcium dynamics plays an important role in the regulation of vascular endothelial cellular functions. In order to probe the intracellular calcium dynamic response under synergistic effect of wall shear stress (WSS) and adenosine triphosphate (ATP) signals, a novel microfluidic device, which provides the adherent vascular endothelial cells (VECs) on the bottom of microchannel with WSS signal alone, ATP signal alone, and different combinations of WSS and ATP signals, is proposed based upon the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…It is noteworthy that the microchannels acts as a low-pass filter are dependent on multiple factors including the biochemical signal frequency, flow rates and signal transporting distance in our previous study [ 20 , 22 ]. Therefore, the biochemical stimuli exposed on cells may be different from expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the microchannels acts as a low-pass filter are dependent on multiple factors including the biochemical signal frequency, flow rates and signal transporting distance in our previous study [ 20 , 22 ]. Therefore, the biochemical stimuli exposed on cells may be different from expected.…”
Section: Discussionmentioning
confidence: 99%
“…By using microfluidic platform, single yeast cells trapped via partially closed valves in response to short repeated pulses of α-factor [ 14 ], single Jurkat T cells in response to low frequency H 2 O 2 [ 15 , 16 ] and oscillatory Ca 2+ stimulus [ 17 ] in microstructure well-trapping chip. Alternatively, single adherent cells cultured on the bottom of the microfluidic channel were also investigated for their responses induced by temporal varying stimulus, such as adenosine triphosphate (ATP) pulse stimulus on NIH-3T3 cells [ 18 ], HeLa cells [ 19 ] and human umbilical vein vessel endothelial cells (HUVECs) [ 20 ], as well as a brief bacterial lipase pulses on single macrophage cell [ 21 ]. Nevertheless, there are two issues to be considered carefully in the study of dynamic external stimuli-induced cell responses in microfluidic channels.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, microfluidics allows for the introduction of flow-based shear stress, which is known to mechanically couple blood-flow to endothelial function 9,10 . Although numerous microfluidic designs for endothelial studies have been reported in the past two decades, most of them applied a 2D extracellular matrix (ECM; e.g., a coated layer of collagen and/or fibronectin) for the cells, without considering the possible 3D structures of the native ECM [11][12][13][14][15][16][17] . In vivo, endothelial cells rest on a 3D surface called the basement membrane (BM), which lines blood vessels 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Key practical features of the RID module include (i) an accessible fabrication process with rapid assembly (<2 min), (ii) low device cost (<$0.50 at lab prototype level), and (iii) press-to-fit tubing connections to simplify component integration. Controlled shear stimulation of cultured cells is a hallmark capability in microfluidic systems that enables quantitative correlation between applied fluid-induced wall shear stresses (WSS) and cellular responses including endothelial cell alignment [18], calcium signaling [19], and barrier formation [20,21]. Thus, we validated RID performance by characterizing bubble removal capabilities ranging from nanoliter to microliter volume bubbles at flow rates required to apply physiological WSS to cultured mammalian cells within standard geometry microfluidic channels.…”
Section: Introductionmentioning
confidence: 99%